The ϒ(nS)→BcDs, BcDd decays with perturbative QCD approach - Junfeng Sun; Yueling Yang; Qingxia Li; Haiyan Li; Qin Chang; Jinshu Huang (Physics Letters B, 2016)
The ϒ(nS)→BcDs, BcDd weak decays are studied with the pQCD approach firstly. It is found that branching ratios Br(ϒ(nS)→BcDs)∼O(10−10) and Br(ϒ(nS)→BcDd)∼O(10−11), which might be measurable in the future experiments.